Biomarkers for predicting efficacy of chimeric antigen receptor T cell therapy and their detection methods - Bo Zou; Yanzhou Song; Ning Li; Zhongyi Fan; Jie Li; Yuanzheng Peng; Wanshan Wei; Yuzi Zhang; Yinan Su; Xianmin Meng; Hongzhou Lu; Xingding Zhang; et al. (iLabmed)
Abstract Cancer immunotherapy has emerged as the fourth most prevalent approach to tumor treatment, alongside surgery, radiotherapy, and chemotherapy. After several decades of development, chimeric antigen receptor T (CAR‐T) cell therapy, a promising branch of adoptive T‐cell therapy, has demonstrated superior efficacy and safety in comparison to other cell therapies in the treatment of cancer. At present, CAR‐T cells are predominantly used to treat hematological malignancies, although their application in solid tumors is being readily investigated. Although numerous studies have examined the biomarkers associated with the safety of CAR‐T cell therapy, few have evaluated predictors of CAR‐T cell therapeutic efficacy. Thus, the primary objective of this review article was to provide a comprehensive overview of the factors predicting the efficacy of CAR‐T cell therapy, with a particular focus on biomarkers and their detection methods.